2005
DOI: 10.1111/j.1600-0765.2005.00779.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and pathogenic differences of Porphyromonas gingivalis fimA genotypes in patients with aggressive periodontitis

Abstract: These results suggest that differences in virulence exist among different fimA genotypes. Coadherence with other pathogens in P. gingivalis fimA type II-associated aggressive periodontitis and quantitative increases in P. gingivalis in fimA type I-associated aggressive periodontitis are related to this virulence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 26 publications
7
68
0
3
Order By: Relevance
“…The results that we obtained with cultured isolates confirmed the results of clinical investigations that fimA genotypes II and fimA IV are predominant in chronic periodontitis-affected sites (2, 7). Other investigators (35,36,38) have confirmed that genotype II is the most prevalent genotype at diseased sites, with genotype Ib being the second most prevalent in patients with aggressive or chronic periodontitis. These observations and the results from a similar study with healthy subjects with a predominance of genotypes I, III, and V (3) could indicate a difference in the fimbrillin monomer and, therefore, a difference in the composition of the fimbriae that could be responsible for the variation in the pathogenic potential of the major fimbriae of P. gingivalis.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The results that we obtained with cultured isolates confirmed the results of clinical investigations that fimA genotypes II and fimA IV are predominant in chronic periodontitis-affected sites (2, 7). Other investigators (35,36,38) have confirmed that genotype II is the most prevalent genotype at diseased sites, with genotype Ib being the second most prevalent in patients with aggressive or chronic periodontitis. These observations and the results from a similar study with healthy subjects with a predominance of genotypes I, III, and V (3) could indicate a difference in the fimbrillin monomer and, therefore, a difference in the composition of the fimbriae that could be responsible for the variation in the pathogenic potential of the major fimbriae of P. gingivalis.…”
Section: Discussionmentioning
confidence: 89%
“…In patients with chronic marginal periodontitis, P. gingivalis organisms with fimA genotype II are significantly more prevalent than isolates with other genotypes (2,4,7,35,37,38). Studies concerning the pathogenic potentials of distinct fimA genotypes also indicate that genotype II organisms are more prevalent in patients with aggressive periodontitis (36). The relationship of periodontal health and specific fimA genotypes has also been investigated, and it was found that that fimA genotype I is the most prevalent among P. gingivalis-positive healthy adults, followed by genotype V (3).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Periodontal diseases and inflammation are associated with specific P. gingivalis virulence factors (Tatakis & Kumar, 2005), including fimbriae (Miura et al, 2005;Weinberg et al, 1997), lipopolysaccharides (LPS) (Wang et al, 2002) and gingipains (Kadowaki et al, 1994Pathirana et al, 2007a;Potempa et al, 2000;Yoneda et al, 1990). Gingipains are cysteine proteases produced by P. gingivalis (Kadowaki et al, 1994;Potempa et al, 2000).…”
Section: Introductionmentioning
confidence: 99%